2015
DOI: 10.1177/2211068215584278
|View full text |Cite
|
Sign up to set email alerts
|

Interlaboratory Reproducibility of Blood Morphology Using the Digital Microscope

Abstract: Differential counting of peripheral blood cells is an important diagnostic tool. However, manual morphological analysis using the microscope is time-consuming and requires highly trained personnel. The digital microscope is capable of performing an automated peripheral blood cell differential, which is as reliable as manual classification by experienced laboratory technicians. To date, information concerning the interlaboratory variation and quality of cell classification by independently operated digital micr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 10 publications
0
11
1
Order By: Relevance
“…Comparing five WBC differentials by DI-60 with those by manual count, the correlations were moderate to high except basophils and improved after verification ( Figure 1 ). Several studies have reported that basophil showed a larger variation and a lower correlation because it is a small number of cells and its detection is highly affected depending on where the PBS is read [ 20 , 33 , 34 ]. Similarly in this study, basophils preclassified by DI-60 were unable to perform Passing-Bablok regression.…”
Section: Discussionmentioning
confidence: 99%
“…Comparing five WBC differentials by DI-60 with those by manual count, the correlations were moderate to high except basophils and improved after verification ( Figure 1 ). Several studies have reported that basophil showed a larger variation and a lower correlation because it is a small number of cells and its detection is highly affected depending on where the PBS is read [ 20 , 33 , 34 ]. Similarly in this study, basophils preclassified by DI-60 were unable to perform Passing-Bablok regression.…”
Section: Discussionmentioning
confidence: 99%
“…They concluded that the CellaVision has excellent performance for the five “normal” WBC classes, as well as for blasts . In another study, Riedl et al placed CellaVision instruments in each of four different clinical laboratories in the Netherlands . They were able to demonstrate that the instruments yielded reproducible preclassification results for neutrophils, lymphocytes, monocytes, and eosinophils.…”
Section: Determination Of the Strengths And Weaknesses Of Available Pmentioning
confidence: 99%
“…DM has first been validated for leukocyte differentiation, and good correlations between automated and manual examinations of peripheral blood smears were observed for a number of different cell types (eg, neutrophils, eosinophils, basophils, lymphocytes, and monocytes) . In addition, automated morphology analysis of leukocytes has shown to have good interlaboratory reproducibility and is being used and implemented in routine hematology laboratories worldwide to detect (malignant) leukocyte abnormalities. Automated blood smear analysis also has the possibility to analyze the morphology of RBCs without human interference objectively.…”
Section: Introductionmentioning
confidence: 99%